2021
DOI: 10.1007/s41348-021-00444-z
|View full text |Cite
|
Sign up to set email alerts
|

Zinc phosphate protects tomato plants against Pseudomonas syringae pv. tomato

Abstract: The purpose of this study was to determine whether zinc phosphate treatments of tomato plants (Solanum lycopersicum L.) can attenuate bacterial speck disease severity through reduction of Pseudomonas syringae pv. tomato (Pst) growth in planta and induce morphological and biochemical plant defence responses. Tomato plants were treated with 10 ppm (25.90 µM) zinc phosphate and then spray inoculated with strain DAPP-PG 215, race 0 of Pst. Disease symptoms were recorded as chlorosis and/or necrosis per leaf (%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Other interesting property of nanoZn was the inhibitory activity against P. syringae ( Ps ), the main cause of tomato bacterial speck, a disease that causes severe losses in tomato yield and quality worldwide, occurring particularly during cold and wet springs . We monitored the growth of the bacteria (measuring the optical density at 600 nm) in KB media at pH 4.5, starting from an optical density of 0.1 (Figure a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other interesting property of nanoZn was the inhibitory activity against P. syringae ( Ps ), the main cause of tomato bacterial speck, a disease that causes severe losses in tomato yield and quality worldwide, occurring particularly during cold and wet springs . We monitored the growth of the bacteria (measuring the optical density at 600 nm) in KB media at pH 4.5, starting from an optical density of 0.1 (Figure a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…NanoZn can be considered as an alternative to control plant diseases caused by Ps , the main cause of bacterial speck in tomatoes, which has a relevant impact in crop production worldwide. This would avoid (or significantly reduce) the use of environmentally harmful conventional strategies consisting in the spray of bactericides, such as copper compounds (e.g., copper hydroxide) with or without combination of fungicides or other pest-control chemicals, their application currently being under regulation (e.g., a maximum limit of 4 kg ha –1 year –1 of copper per application has been imposed in Europe) . Therefore, the strategy reported here presents dual agricultural applicability, increasing crop yields and plant nutritional values and simultaneously avoiding the development of significant bacterial-based diseases.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Zn can easily diffuse from the root to the xylem through specific transporters in the plasma membrane, then toward shoots in the transpiration stream. Hence, either in the soil or inside a plant, Zn might act directly against the pathogen by avoiding conidial production and pathogen reproduction in soil ( Luo et al, 2020 ), which may cause systemic acquired tolerance due to a decrease in the pathogen population ( Quaglia et al, 2021 ). Martos et al (2016) findings attributed the dual effect of Zn as a direct inhibitor of fungal pathogen and potential enhancer of fungal-induced systemic resistance by jasmonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, soil application with Zn-based fertilizers has been reported to alleviate biotic stress and increase productivity by boosting the activity of antioxidant enzymes [catalase (CAT), peroxidase (POX), superoxide dismutase (SOD), and polyphenol oxidase (PPO)] against oxidative stress induced by reactive oxygen species (ROS) ( Khan et al, 2018 ; Ahmad et al, 2019 , 2020 ; Shoaib et al, 2020 ; Mansoor et al, 2022 ). Quaglia et al (2021) findings revealed that Zn phosphate induced morphological and biochemical plant defense responses in tomatoes and direct antimicrobial activity against Pseudomonas syringae pv. tomato.…”
Section: Introductionmentioning
confidence: 97%